(untitled) (Research, Society and Development, 2026)
There are multiple perioperative measures to prevent complications, ranging from appropriate patient selection to the use of medications to reduce intraoperative blood loss. The current trend is prevention rather than treatment, and tranexamic acid (TXA) has been tested in multiple surgical procedures. The objective is to demonstrate the usefulness of TXA through intravenous, topical, and oral routes; to increase its use in Aesthetic and Reconstructive Surgery procedures to reduce intraoperative blood loss, as well as to reduce ecchymosis and inflammation, in order to ensure greater patient safety. Material and Methods: A bibliographic review was conducted using PubMed, Elsevier, Google Scholar, Research, and SciELO databases; articles in Portuguese, English, and Spanish were included using “AND” for different terms and “OR” for synonyms, covering the period between 2015 and 2024. Results: Through knowledge of the pharmacokinetics of TXA, we verified that, in addition to its usefulness in preventing hemorrhage, it also plays a role in reducing ecchymosis and inflammation. Conclusions: This study contributes to a better understanding of the use of TXA in preventing bleeding in aesthetic and reconstructive surgeries, as well as its intraoperative and postoperative complications.